PENGEMBANGAN MEDIA PEMBELAJARAN E-COMIC MATERI BIOGRAFI SINGKAT K.H. AHMAD DAHLAN SEBAGAI PENGUATAN NILAI KARAKTER KEMUHAMMADIYAHAN - Nurjanah Janah; Yurdayanti yanti; Fitri Apriani Apriani (Universitas Muhammadiyah Ponorogo, 2022)
E-comic learning media is an important component in providing deficiencies in the Al-Islam learning process in the classroom, this media can also help students to encourage student learning motivation, clarify and simplify abstract concepts and enhance absorption. E-comic media is one of the intermediaries that can attract students' interest in reading a material because it is presented in the form of images accompanied by short text. By utilizing this e-comic, it is hoped that Islamic education learning will focus on the character values of Muhammadiyah.The purpose of this study was to find out how the development and response of students to e-comic material for the short biography of K.H Ahmad Dahlan as strengthening the value of Muhammadiyah character and regeneration. This research uses research and development methods or Research and Development (RD) with development procedures in this RD research using the Four-D Model (4D) design, namely: (1) Define (defining); (2) Design (design); Develop (development); and (4) Disseminate (spread). Data collection in this study was carried out in two ways, namely test and non-test. The test was carried out with Pretest and Posttest. While the non-test is by observation, distributing questionnaires, and documentation. Then the data were analyzed through qualitative and quantitative methods. Through this stage, the results of the research product in the form of e-comic learning media as strengthening character values are that: (1) The feasibility of e-comic learning media products, the average assessment at the validation stage by a team of media experts is 90%; (2) The feasibility of e-comic learning media products on average at the validation stage by the material 1 expert team was obtained at 98%, while the material 2 expert team obtained 96%; (3) Design development is used according to the 4D flow; (4) The results of the feasibility of small-scale trials are 95% while large-scale trials are 98%..